2022
DOI: 10.3390/ijerph19073986
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Daily Life, Physical Exercise, and General Health among Older People with Type 2 Diabetes: A Qualitative Interview Study

Abstract: The COVID-19 pandemic has resulted in significant alterations to and implications for the lives of millions of people, and especially for those with pre-existing medical conditions. The aim of this study was to explore the lived experience of older people with type 2 diabetes mellitus (T2DM) throughout the first 9 months of the pandemic, with emphasis on the habits of physical exercise. We conducted a qualitative study using semi-structured interviews. The data consist of telephone interviews of seventeen olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
0
12
0
3
Order By: Relevance
“…Disruption of healthcare is a widely discussed impact of the pandemic. A universally decreased health service utilization for non-COVID-19 conditions [56] has been reported in many countries [4] , [12] , [57] , [58] , characterized by reduced health service hours due to lockdowns, dwindling human resource availability due to medical source re-allocation, and hesitancy to seek care due to fears of contracting the virus during the pandemic; such change may result in challenging management of diabetes in the long term, even though it takes time to be revealed. One study [59] examined the impact of the 2003 SARS epidemic retrospectively and found a short-term dramatic decline in healthcare utilization would lead to increased diabetic mortality one year after the outbreak [relative risk:1.08 (CI: 1.03 – 1.15)].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Disruption of healthcare is a widely discussed impact of the pandemic. A universally decreased health service utilization for non-COVID-19 conditions [56] has been reported in many countries [4] , [12] , [57] , [58] , characterized by reduced health service hours due to lockdowns, dwindling human resource availability due to medical source re-allocation, and hesitancy to seek care due to fears of contracting the virus during the pandemic; such change may result in challenging management of diabetes in the long term, even though it takes time to be revealed. One study [59] examined the impact of the 2003 SARS epidemic retrospectively and found a short-term dramatic decline in healthcare utilization would lead to increased diabetic mortality one year after the outbreak [relative risk:1.08 (CI: 1.03 – 1.15)].…”
Section: Discussionmentioning
confidence: 98%
“…A large proportion of health resources were reallocated to COVID-19 or emergency care [11] . People were reluctant to seek medical assistance due to fear of risking exposure to the infection [4] , [12] , [13] . For people with T2DM who require consistent monitoring of symptoms and timely treatment adjustment, such as personalized glycemic control protocol [14] , the disruption of care created new barriers to managing the disease, which may have resulted in poor health outcomes or incidence of diabetes-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should employ qualitative methods to uncover the nuances in these associations and to explore potential mechanisms. For example, qualitative interviews with a sample of people with type 2 diabetes revealed reduced motivation due to loneliness and reduced social contact inhibited engagement in physical activity during the COVID-19 pandemic [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the normalized management of the epidemic, more attention has been paid to the loneliness of T2DM patients. The epidemic has increased the difficulty of disease management, which is no different from making things worse for diabetics (Leite et al, 2022).…”
Section: Backg Rou N Dmentioning
confidence: 99%